Identification and colonization of endophytic fungi from soybean (Glycine max (L.) Merril) under different environmental conditions - Pimentel,Ida Chapaval (2006)
A total of 297 endophytic fungi were isolated from 1728 leaf and stem fragments collected about twenty and forty days after germination from soybean (Glycine max (L.) Merril) plants grown in the field and a greenhouse. The fungi belonged to eight groups, six dematiaceous genera (Alternaria, Cladosporium, Chaetomium, Curvularia, Drechslera and Scopulariopsis) and the non-dematiaceous genera Acremonium, Aspergillus, Colletotrichum, Fusarium, Paecilomyces and Penicillium along with some Mycelia sterilia.. There were qualitative and quantitative differences in the type and number of isolates obtained from greenhouse and field-grown plants, with more isolates being obtained from the latter. No difference was found in the number of fungi isolated from leaves and stems irrespective of where the plants was grown. For was field-grown plants, the number of isolates decreased as the plants aged and more fungi were found in tissues near the soil, while for greenhouse-grown plants the number of isolates increased as the plants aged but in this case no more fungi were isolated from those tissues nearer the soil. These results could have biotechnological relevance for the biological control of pests or plant growth promotion.